Women, Faith, and Educational Leadership in Colonial Asia: The Case of Rahmah El Yunusiyah - Oki Dermawan; Zohaib Hassan Sain; Saim Kayadibi (CV. FOUNDAE, 2026)
This article examines the educational leadership of Rahmah El Yunusiyah in colonial Indonesia, with particular attention to her contribution to Muslim women’s education in Southeast Asia. Using a historical qualitative method based on published historical studies, documentary sources, and interpretive analysis, the study explores how Rahmah El Yunusiyah developed Diniyah Puteri as an alternative educational institution for girls under colonial rule. The findings show that her leadership was expressed through three main strategies: building an institution outside colonial educational priorities, legitimizing women’s education through Islamic values, and combining religious instruction with modern pedagogical practices. These strategies enabled Rahmah not only to challenge colonial and patriarchal restrictions at the local level, but also to offer a model of Muslim women’s education that gained wider recognition in the Malay-Indonesian world. Her contribution to Southeast Asia lies in demonstrating that Islamic schooling for girls could become a legitimate space for women’s intellectual formation, social participation, and leadership development. The study argues that Rahmah El Yunusiyah represents a non-Western model of educational leadership rooted in faith, social reform, and women’s empowerment. This case contributes to broader discussions on women’s leadership, Islamic education, and the history of education in colonial Asia.